UNIVERSITY CHATGPT: FRIEND OR FOE? - Leila BELKAIM (Universitaria Publishing House, Craiova, 2023)
In this article, we highlight the key tool called "ChatGPT". In the era of artificial intelligence and the digitalization of education, the university teacher must innovate his teaching practices in front of the GPT Chat which is talked about too much. And this, to give its students quality teaching practices and adapt to the requirements of the software. As a result, getting started with the ChatGPT tool has a significant impact on the development of teachers' digital skills. This allows them to take charge of their own teaching in terms of needs, commitment and professional rhythm. However, the ChatGPT tool is currently a sublimation and a rejection or even a commotion for the university teacher and the rest of the world. In the teaching sector the debate is divided between ethics and anethics, therefore, is the teacher able to detect plagiarism and similarity in the answers of his students? For the sake of academic integrity, teachers should find smart and rational learning assessment solutions to block all possibilities of plagiarism with ChatGPT. Our objective is to show how the evaluation of work in higher education is done under the effect of the ChatGPT challenge. The mobilization of quantitative and qualitative methods in our research will provide us with conclusive answers to the question of the new challenges of correcting student evaluations in the context of ChatGPT.